Hepatotoxicity in HIV-infected children and adolescents on antiretroviral therapy - Gil, Ana Cecilia Montes; Lorenzetti, Raquel; Mendes, Gun Bergsten; Morcillo, André Moreno; Toro, Adyléia Aparecida Dalbo Contrera; Silva, Marcos Tadeu Nolasco da; Vilela, Maria Marluce dos Santos (São Paulo Medical Journal, 2007)
CONTEXT AND OBJECTIVE: Adverse drug reactions are a signifi cant problem in patients on antiretroviral therapy (ART). We determined liver enzyme elevation frequencies in HIV-infected children and adolescents receiving ART, and their association with risk factors. DESIGN AND SETTING: Cross-sectional study, at the Pediatrics Immunodefi ciency Division, University Hospital, Universidade Estadual de Campinas. METHODS: Medical records of 152 children and adolescents (54.6% male; median age 7.48 years) were analyzed, with a mean of 2.6 liver enzyme determinations per patient. Clinically, patients were classifi ed in categories N (6), A (29), B (78) and C (39). Serum levels of aspartate aminotransferase and alanine aminotransferase were evaluated. Hepatotoxicity was scored as grade 1 (1.1-4.9 times upper limit of normality, ULN), grade 2 (5.0-9.9 times ULN), grade 3 (10.0-15.0 times ULN) and grade 4 (> 15.0 times ULN). To assess hepatotoxicity risk factors, odds ratios (OR) and adjusted odds ratios (aOR) for age, gender, TCD4+ cell count, viral load and medication usage were calculated. RESULTS: We observed grade 1 hepatotoxicity in 19.7 % (30/152) patients. No cases of grade 2, 3 or 4 were detected. There was a signifi cant association between hepatotoxicity and use of sulfonamides (OR, 3.61; 95% confi dence interval (CI), 1.50–8.70; aOR, 3.58; 95% CI, 1.44–8.85) and antituberculous agents (OR, 9.23; 95% CI, 1.60–53.08; aOR, 9.05; 95% CI, 1.48–55.25). No toxicity was associated with ART. CONCLUSIONS: One fi fth of patients experienced mild hepatotoxicity, attributed to antituberculous agents and sulfonamides. Our results suggest that ART was well tolerated.